Depresión y su influencia en el consumo de drogas en una persona privada de libertad - Paredes Escobar, Sully Silvana (2020)
Depression is a frequent mental disorder, characterized by the presence of sadness, loss of interest or pleasure, feelings of guilt or lack of self-esteem, sleep or appetite disorders, deprivation of liberty refers to the criminal ordinance that is assigned to the person who has committed a criminal action, this case study is carried out with the objective of finding the influence of depression on drug use in a person deprived of liberty. In order to find the effects on the emotional area of the person, different diagnostic assessment techniques and instruments were used, such as the Beck Depression Inventory, to assess the underlying depression rates and the Alcohol, tobacco and alcohol consumption test. substances (ASSIST), serving as a great support at the time of evidences the symptomatic picture, together with the data obtained from the Psychological Interview.